2013
DOI: 10.5267/j.msl.2013.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Co-determination of capital structure and stock returns in banking industry using structural equation modeling

Abstract: Capital structure plays essential role on financial strength of business units and there are literally many studies to confirm the relationship between capital structure and return growth. In this paper, we re-examine this relationship by investigating on 12 Iranian private banks using structural equation modelling over the period 2005-2011. The proposed study of this paper designs a questionnaire and distributes it among experts and analyse it use LISREL software package. The result indicates that there is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
2
1
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 19 publications
6
2
1
2
Order By: Relevance
“…This statement in line with a study by (Al Ani & Al Amri, 2015) found that firm size positively influences leverage. This is in line with a study by (Chen et al, 2014;Cheng & Tzeng, 2011;Lemma & Negash, 2013;Taghavi et al, 2013;Thi Hang & Jay Hung, 2016;Yang et al, 2010). However, it is different from a study by (Chandra, 2015;Fauzi et al, 2013;Chandra et al, 2019;Tse & Rodgers, 2014).…”
Section: Firm Sizesupporting
confidence: 82%
See 4 more Smart Citations
“…This statement in line with a study by (Al Ani & Al Amri, 2015) found that firm size positively influences leverage. This is in line with a study by (Chen et al, 2014;Cheng & Tzeng, 2011;Lemma & Negash, 2013;Taghavi et al, 2013;Thi Hang & Jay Hung, 2016;Yang et al, 2010). However, it is different from a study by (Chandra, 2015;Fauzi et al, 2013;Chandra et al, 2019;Tse & Rodgers, 2014).…”
Section: Firm Sizesupporting
confidence: 82%
“…This condition will stimulate the increase in the company's risk and lead investors to consider the application for a loan from the company. This result is not in line with a study by (Chang et al, 2014;Taghavi et al, 2013;Yang et al, 2010). H3: Uniqueness influenced capital structure in the Indonesia manufacturing sector.…”
Section: Uniquenesscontrasting
confidence: 82%
See 3 more Smart Citations